Digital Banking Payment Services and Customer Satisfaction: Evidence From A Selected Liquefied Petroleum Gas Business - Daniel Oluwaseun Oyalakun; Omotayo Joseph Oyeniyi; Mathias Adedayo Opele; Sekinat Arike Sanni-Bamigbade (Journal of Business and Management Inaba, 2026)
This research focused on determining the effects of digital banking payment services on customer satisfaction with a selected retail liquefied petroleum gas (LPG) business in Ogun State, Nigeria. The study used a survey research design, in which one hundred (100) bulk dealer customers who use digital banking payment services apart from cash in their mode of payment were chosen as the sample size, although only ninety-seven (97) were able to complete the survey. Questionnaires were used to generate data that was used. In testing the hypotheses in this study, it was found that digital banking payment services have contributed to customer satisfaction. The study recommends that small business owners and their managers should consistently take the factors tested above into consideration when deciding on the digital banking payment services as a mode of payment, as it affects customer satisfaction.